Hybrid numeric-analytic method for solving chaotic system - Razali, NurIsnida; Chowdhury, Md. Sazzad Hossien; Asrar, Waqar (2013)
In this paper, a numerical scheme based on adaption of standard Adomian decomposition method (ADM) is applied to the chaotic Lü system. Then, the standard ADM is converted into a hybrid numeric-analytic method called the multistage ADM (MADM). Numerical comparisons with the standard ADM and the fourth-order Runge-Kutta method (RK4) is made in order to prove that MADM is the reliable method for nonlinear problems